Direct electrical and mechanical characterization of in situ generated DNA between the tips of silicon nanotweezers (SNT). Issue 11 (10th May 2016) - Karsten, Stanislav L.; Kumemura, Momoko; Jalabert, Laurent; Lafitte, Nicolas; Kudo, Lili C.; Collard, Dominique; Fujita, Hiroyuki
Abstract : Expanding sensor capabilities with direct DNA synthesis on the tips of silicon nano-tweezers (SNTs). The figure shows a DNA bundle between the SNT tips. Abstract : Previously, we reported the application of micromachined silicon nanotweezers (SNT) integrated with a comb-drive actuator and capacitive sensors for capturing and mechanical characterization of DNA bundles. Here, we demonstrate direct DNA amplification on such a MEMS structure with subsequent electrical and mechanical characterization of a single stranded DNA (ssDNA) bundle generated between the tips of SNT via isothermal rolling circle amplification (RCA) and dielectrophoresis (DEP). An in situ generated ssDNA bundle was visualized and evaluated via electrical conductivity ( I – V ) and mechanical frequency response measurements. Colloidal gold nanoparticles significantly enhanced ( P < 0.01) the electrical properties of thin ssDNA bundles. The proposed technology allows direct in situ synthesis of DNA with a predefined sequence on the tips of a MEMS sensor device, such as SNT, followed by direct DNA electrical and mechanical characterization. In addition, our data provides a "proof-of-principle" for the feasibility of the on-chip label free DNA detection device that can be used for a variety of biomedical applications focused on sequence specific DNA detection.